2014
DOI: 10.1007/s40684-014-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

An agile operations management system for green factory

Abstract: The globalization of suppliers and personalization of customers require new manufacturing strategy for environmental issues, region's special regulation and energy besides manufacturing factors from manufacturers. In this study, green factory is defined as a manufacturing floor that reduces waste elements such as extra work, energy, time and cost through quickly responding to external uncontrollable changes like a regulation, due date and supply. Therefore, the green factory should respond by establishing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…The energy cost has been also optimized taking into account the cost fluctuation and rescheduling the production accordingly. 22,23 Also an analysis of the available database to access green manufacturing data has been developed. 24 For modern machining centres is proved that the energy required by the ancillary systems is usually larger than the one needed by the spindle, some solutions could hence be found to reduce this value.…”
Section: Introductionmentioning
confidence: 99%
“…The energy cost has been also optimized taking into account the cost fluctuation and rescheduling the production accordingly. 22,23 Also an analysis of the available database to access green manufacturing data has been developed. 24 For modern machining centres is proved that the energy required by the ancillary systems is usually larger than the one needed by the spindle, some solutions could hence be found to reduce this value.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma and Kodali (2008) highlighted the need of lean manufacturing, total quality management and SM as pillars to attain manufacturing excellence. Jo et al (2014) have discussed the importance of integrating agile principles with sustainable principles to achieve better results in the field of SP. In another considerable effort, Yanga et al (2012) have presented the strategic role of total quality management tools to implement SP strategy effectively in the organization.…”
Section: Integration With Other Manufacturing Practicesmentioning
confidence: 99%
“…Bashkite and Karaulova (2012) have reported that integration of lean and sustainable principles had helped in securing 30% extra savings to the organizations compared to using lean strategy alone. To achieve better results in various circumstances, many researchers (Piercy and Rich, 2015;Jo et al, 2014;Yanga et al, 2012;Mollenkopf et al, 2010) have attempted to integrate sustainable principles with other philosophies like lean, agile and total quality management. This study urges the research community to perform in-depth analysis of integrating sustainable philosophy with other philosophies and communicate all the benefits back to the community.…”
Section: Integration With Other Manufacturing Practicesmentioning
confidence: 99%
“…This wave of green supply chain management counseling, you need to clearly inform suppliers of green specification requirements related to content, dismantling methods, content and format of information to fill in the declaration described, with the flow and delivery schedule, simultaneous testing and certification, auditing, etc. and other relevant measures to ensure that incoming conform itself with the customer's green specifications, but also in order to enhance physical fitness and preparedness of the supplier of green product management; also need to be switched with lead free solder process equipment and management processes, implementation staff education and training, in order to confirm the incoming and process which will not produce pollution, to ensure that products meet green specifications [24][25][26][27] as Fig. 1.…”
Section: -23mentioning
confidence: 99%